If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(4x + 1) = 3(12x + -3) Reorder the terms: 7(1 + 4x) = 3(12x + -3) (1 * 7 + 4x * 7) = 3(12x + -3) (7 + 28x) = 3(12x + -3) Reorder the terms: 7 + 28x = 3(-3 + 12x) 7 + 28x = (-3 * 3 + 12x * 3) 7 + 28x = (-9 + 36x) Solving 7 + 28x = -9 + 36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36x' to each side of the equation. 7 + 28x + -36x = -9 + 36x + -36x Combine like terms: 28x + -36x = -8x 7 + -8x = -9 + 36x + -36x Combine like terms: 36x + -36x = 0 7 + -8x = -9 + 0 7 + -8x = -9 Add '-7' to each side of the equation. 7 + -7 + -8x = -9 + -7 Combine like terms: 7 + -7 = 0 0 + -8x = -9 + -7 -8x = -9 + -7 Combine like terms: -9 + -7 = -16 -8x = -16 Divide each side by '-8'. x = 2 Simplifying x = 2
| 92x+31=72 | | -3x+9=30-6x | | 2c/10=24 | | (5c+6)(5c-6)=0 | | 2x^2-4x-44=0 | | 53a-143=42a+8 | | 3x=6-x | | 18-t/20=-9 | | 3s/5=-21 | | x^2-15x+9=0 | | n(n-6)=7 | | 25x(x+4)=10x-81 | | 17b+3=-422 | | 18=18y-18 | | 3c+45=7.2-6c | | 7m^2-2m+2=0 | | 21=6m-9 | | -7+z/4=0 | | -7m^2+2m-2=0 | | (x-10)+(x+2)=90 | | 6x+(-3)=117 | | 4(y+7)-7y=37 | | 6s-27=-19+4s | | 8x-143=-127 | | 9n-26=9+4n | | 436x-789=-571 | | 23x^2-20=0 | | -13x+28=-11 | | Y^2-.6y+.1=0 | | Y^2-.6y+.1111111111=0 | | 6x+18=4x+2 | | 3b(4-2b)-6b=-b(6b+7)+104 |